Fairies, Demons, and Nature Spirits 'Small Gods' at the Margins of Christendom (Palgrave Historical Studies in Witchcraft and Magic, 2018)
This book examines the fairies, demons, and nature spirits haunting the margins of Christendom from late-antique Egypt to early modern Scotland to contemporary Amazonia. Contributions from anthropologists, folklorists, historians and religionists explore Christian strategies of encompassment and marginalization, and the 'small gods' undisciplined tendency to evade such efforts at exorcism. Lurking in forest or fairy-mound, chuckling in dark corners of the home or of the demoniac's body, the small gods both define and disturb the borders of a religion that is endlessly syncretistic and in endless, active denial of its own syncretism. The book will be of interest to students of folklore, indigenous Christianity, the history of science, and comparative religion.